Case Study of Embroidery Craft Application in Barung-Barung Balantai, Koto XI Tarusan Subdistrict, South Pesisir Regency, West Sumatra: Gus Fitri's Embroidery House - Mahmudah, Fitriah; Yusmerita, Yusmerita (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2024)
This study aims to describe the motifs and techniques of embroidery application at Gus Fitri's Embroidery House, Barung-Barung Balantai, Koto XI Tarusan Subdistrict. The research method used is descriptive qualitative, with primary data obtained through direct interviews with the owner and workers at Gus Fitri's Embroidery House. Data collection was conducted through interviews, observations, and documentation, with data validity verified through triangulation and member checks. Data analysis was carried out through data reduction, data presentation, data verification, and conclusion drawing. The results show that the embroidery application motifs at Gus Fitri's Embroidery House are generally plant motifs, such as jasmine flowers, orchids, bamboo, sunflowers, and lotuses. The embroidery application technique includes the design of the motif, the determination of the motif placement, the transfer of the motif onto the fabric, the attachment of the motif to the material, the basting stitch, and the backstitch. This study provides insight into the uniqueness and diversity of embroidery application motifs in Indonesia, especially in West Sumatra, and highlights the importance of preserving and developing traditional crafts as part of cultural heritage.